Integrasi Nilai Keislaman Pada Bahan Ajar Ilmu Pengetahuan Alam Di Madrasah Tsanawiyah Yayasan Pondok Pesantren Darul Hidayah Dusun Pomo Desa Ampel Kecamatan Wuluhan Kabupaten Jember: Integration of Islamic Values into Science Teaching Materials at Madrasah Tsanawiyah of the Darul Hidayah Islamic Boarding School Foundation, Pomo Hamlet, Ampel Village, Wuluhan District, Jember Regency - Umi Farihah; Dimas Danar Septiadi (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2018)
The low motivation and learning outcomes of middle school students in science are caused by the lack of integration between science and Islamic values in teaching materials and teacher-centered learning approaches. This development research aims to produce science teaching materials integrated with Islamic values that are valid, practical, and effective based on the Plomp model. The development was carried out through four phases: initial investigation, design, realization, and testing, evaluation, and revision. Product validity was assessed through expert validation, practicality through observation sheets of student and teacher activities, and effectiveness through learning achievement tests and student response questionnaires. The results showed that the teaching materials were declared valid with an average score of 3.3, and the learning achievement test was very valid with a score of 3.58. Practicality fell into the very practical category, and effectiveness was demonstrated by 82.21% positive student responses and a test reliability of 0.57. It is concluded that science teaching materials integrated with Islamic values are feasible to use and recommended to improve the quality of science learning in madrasahs. Rendahnya motivasi dan hasil belajar IPA siswa MTs disebabkan oleh kurangnya keterkaitan antara sains dan nilai keislaman dalam bahan ajar serta pendekatan pembelajaran yang masih berpusat pada guru. Penelitian pengembangan ini bertujuan untuk menghasilkan bahan ajar IPA terintegrasi nilai Islam yang valid, praktis, dan efektif berdasarkan model Plomp. Pengembangan dilakukan melalui empat fase: investigasi awal, desain, realisasi, serta uji coba, evaluasi, dan revisi. Validitas produk dinilai melalui validasi ahli, kepraktisan melalui lembar pengamatan aktivitas siswa dan guru, serta keefektifan melalui tes hasil belajar dan angket respons siswa. Hasil penelitian menunjukkan bahwa bahan ajar dinyatakan valid dengan skor rata-rata 3,3, dan tes hasil belajar sangat valid dengan skor 3,58. Kepraktisan berada pada kategori sangat praktis, dan keefektifan ditunjukkan oleh respons positif siswa sebesar 82,21% serta reliabilitas tes sebesar 0,57. Disimpulkan bahwa bahan ajar IPA terintegrasi nilai keislaman layak digunakan dan direkomendasikan untuk meningkatkan kualitas pembelajaran IPA di madrasah.